2021
DOI: 10.21203/rs.3.rs-285837/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Transition Readiness in Adolescents with Rheumatic Diseases: A Cross-Sectional Study

Abstract: Background: Most childhood-onset rheumatic diseases are chronic health conditions, which need long-term care throughout adulthood. A well-organized transition care is challenging and patient assessment of transition skills is needed for transfer preparation to adult care setting. The Transition Readiness Assessment Questionnaire (TRAQ) is used to assess transition skills in chronically ill patients. Currently, limited transition skill assessment data exist in pediatric patients with rheumatic diseases, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Second, information on AYAs' socio-economic status, medical complexity or comorbidity and proxy markers of autonomy (e.g. current living situation, pregnancy) was not collected, even though these may influence their level of transition readiness (Anelli et al, 2019;Culen et al, 2019;González et al, 2017;Kittivisuit et al, 2021;Wood et al, 2014). Finally, most subscales of the TRAQ showed low reliability estimates, which is often found in scales with few items (median = 4) (Streiner, 2003), and a number of TRAQ items may not apply to specific clinical populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, information on AYAs' socio-economic status, medical complexity or comorbidity and proxy markers of autonomy (e.g. current living situation, pregnancy) was not collected, even though these may influence their level of transition readiness (Anelli et al, 2019;Culen et al, 2019;González et al, 2017;Kittivisuit et al, 2021;Wood et al, 2014). Finally, most subscales of the TRAQ showed low reliability estimates, which is often found in scales with few items (median = 4) (Streiner, 2003), and a number of TRAQ items may not apply to specific clinical populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, lower overall transition readiness has been associated with younger age (Anelli et al, 2019;Wood et al, 2014), being male (Chapados et al, 2021;González et al, 2017), cognitive impairment (Sawicki et al, 2009) and lower health literacy beliefs (Prussien et al, 2022). Beyond global scores, few studies identified predictors of transition readiness at the subscale level (Kittivisuit et al, 2021;Wood et al, 2014), and several factors associated with transition readiness have yet to be assessed, such as AYAs' psychosocial functioning (Gutierrez-Colina et al, 2020;Kittivisuit et al, 2021). Identifying AYA transition readiness skills and skill gaps, both in general and at transfer age, could be a valuable means of promoting a successful transition to the adult care system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation